Less Talk, More Builds: The Mixed-Income Residential Tower Model of the University of Winnipeg Community Renewal Corporation - Jackson, Edward T.; Read, Jeremy E. (Engaged Scholar Journal, 2024)
The search for and replication of scalable models for affordable housing amid North America’s housing insecurity crisis has been frustratingly slow. Governments are flailing—and, so far, failing—as they try to put in place the necessary policies and incentives for the private, public, and non-profit sectors to accelerate the construction of the millions of new affordable units required to confront the crisis. This paper highlights one model whose replication is underway in Winnipeg’s downtown core: that of a mixed-income, mixed-use residential tower offering nearly half of its units at affordable rental prices for marginalized residents and designed, built, and managed with a deep commitment to multi-dimensional sustainability. The catalyst for this initiative is the University of Winnipeg Community Renewal Corporation (UWCRC), a non-profit foundation that works in partnership with community organizations and is now Winnipeg’s leading social real estate developer. The Corporation is the second component of the model. While there are no perfect strategies for solving the housing crisis, UWCRC’s approach deserves to be widely known, deeply studied, and rapidly adapted and replicated at scale by universities, colleges, and other public institutions in urban centres throughout North America. Engaged scholars can play important roles in this effort.